PENGARUH FASILITAS KESEHATAN TERHADAP KEPUASAN PASIEN DI PUSKESMAS SALUGATTA KECAMATAN BUDONG-BUDONG KABUPATEN MAMUJU TENGAH - Febrian, Muhammad; Malik, Ihyani; Syukri, Syukri (Universitas Muhammadiyah Makassar, 2025)
The aim of this research is to find out how much influence health facility variables have on patient satisfaction variables at the Salugatta Community Health Center, Budong-Budong District, Central Mamuju Regency. This research uses quantitative research methods with descriptive research type. The data collection technique was through a survey using a questionnaire given to patients at the Salugatta Health Center in January with a sample size of 88 respondents. The results of this study show that health facilities have a significant effect on patient satisfaction. And the results of the health facility hypothesis test (X) have a positive effect on patient satisfaction (Y). This is indicated by the value of tcount ttable with a value of 18.123 1.987 with a significance value of 0.001 0.05. Based on the coefficient of determination (R Square) of 0.792, which means the influence of health facilities (X) on patient satisfaction (Y) is 79% while the rest is influenced by other factors. It is hoped that the implications of this research will be for the Central Mamuju Regency government to be able to improve existing infrastructure at the Salugatta Community Health Center so that it can increase patient satisfaction, because health facilities are very important for the community.